2004
DOI: 10.1093/ndt/gfh261
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of N-acetylcysteine in patients at risk for contrast nephropathy: decrease in oxidant stress-mediated renal tubular injury

Abstract: In chronic renal failure patients, the improvement in renal function induced by post-radiocontrast administration of N-acetylcysteine is strongly associated with suppression of oxidant stress-mediated proximal tubular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 17 publications
4
82
1
7
Order By: Relevance
“…Use of N-acetylcysteine, a free radical scavenger and renal vasodilator, 67 has produced mixed results in the prevention of contrast-induced nephropathy. The largest and most recent meta-analyses showed a benefit from the use of N-acetylcysteine in high-risk patients; however, there was considerable variability in both dosing and efficacy.…”
mentioning
confidence: 99%
“…Use of N-acetylcysteine, a free radical scavenger and renal vasodilator, 67 has produced mixed results in the prevention of contrast-induced nephropathy. The largest and most recent meta-analyses showed a benefit from the use of N-acetylcysteine in high-risk patients; however, there was considerable variability in both dosing and efficacy.…”
mentioning
confidence: 99%
“…[4][5][6]53 In that population, the prevalence of contrast-induced nephropathy can reach up to 50%, 50 which was observed in initial, older studies. In more recent studies, using preventive maneuvers, the incidence of CN is around 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous hydration with 0.9% SS) 0.9% SS 1 mL/kg/h, 12 hours before and 12 hours after the procedure Several randomized studies and metaanalyses 30,[32][33][34] 0.9% SS is superior to 0.45% SS 23,32 Sodium bicarbonate (154 mEq/L) NaHCO3 3 mL/kg/h, 1 hour before the procedure and 1 mL/kg/h, 6 hours after the procedure Several randomized studies and meta-analyses 32,[49][50][51][52][53][54] Dilute 154 mL of 8.4% sodium bicarbonate in 846 mL of distilled water for obtaining the solution Type of contrast medium Low-osmolality or iso-osmolality contrast medium Some randomized studies and a few meta-analyses [26][27][28] The literature is still controversial whether isoosmolality contrast medium is superior to low-osmolality contrast medium 29 N-acetyl cysteine 600 mg, orally, 12/12 hours, 24 hours before and after the procedure Still controversial 54,55 Large ongoing multicenter study 56 …”
Section: Most Used Methods Evidence Level Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may diminish the oxidative stress markers ( (Drager etal., 2004;Efrati etal., 2003) and / or its vasodilatory effect (Fishbane etal., 2004;Stenstorm etal., 2008).CM decrease urinary nitric oxide and NAC may inhibit this effect of CM. But it has been shown that NAC has no effect on F2-isoprostane a known marker of oxidative stress (Efrati etal., 2003).…”
Section: N-acetyl Cysteine (Nac)mentioning
confidence: 99%